Bmi1 regulate tooth and mandible development by inhibiting p16 signal pathway - Yin, Ying (J Cell Mol Med, 2021)
To determine whether the deletion of p16 can correct tooth and mandible growth retardation caused by Bmi1 deficiency, we compared the tooth and mandible phenotypes of homozygous p16‐deficient (p16(−/−)) mice, homozygous Bmi1‐deficient (Bmi1(−/−)) mice, double homozygous Bmi1 and p16‐deficient (Bmi1(−/−)p16(−/−)) mice to those of their wild‐type littermates at 4 weeks of age by radiograph, histochemistry and immunohistochemistry. Results showed that compared to Bmi1(−/−) mice, the dental mineral density, dental volume and dentin sialoprotein immunopositive areas were increased, whereas the ratio of the predentin area to total dentin area and that of biglycan immunopositive area to dentin area were decreased in Bmi1(−/−)p16(−/−) mice. These results indicate that the deletion of p16 can improve tooth development in Bmi1 knockout mice. Compared to Bmi1(−/−) mice, the mandible mineral density, cortical thickness, alveolar bone volume, osteoblast number and activity, alkaline phosphatase positive area were all increased significantly in Bmi1(−/−)p16(−/−) mice. These results indicate that the deletion of p16 can improve mandible growth in Bmi1 knockout mice. Furthermore, the protein expression levels of cyclin D, CDK4 and p53 were increased significantly in p16(−/−) mice compared with those from wild‐type mice; the protein expression levels of cyclin D and CDK4 were decreased significantly, whereas those of p27 and p53 were increased significantly in Bmi1(−/−) mice; these parameters were partly rescued in Bmi1(−/−)p16(−/−) mice compared with those from Bmi1(−/−) mice. Therefore, our results indicate that Bmi1 plays roles in regulating tooth and mandible development by inhibiting p16 signal pathway which initiated entry into cell cycle.